PENGARUH KEPEMIMPINAN, KOMPENSASI DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BAKTI NUGRAHA YUDA (ENERGY) PLTU BATURAJA - Noviansyah Noviansyah; Yunita Sari; Cici Paramti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
The Influence of Leadership, Compensation and Work Placement on Employees’ Performance at PT. Bakti Nugraha Yuda (Energy) PLTU Baturaja. This study aims to determine the influence of leadership, compensation and work placement on employees’ performance at PT. Bakti Nugraha Yuda (Energy) PLTU Baturaja. In conducting the analysis, multiple linear regression was used. Based on data analysis and partial discussion, Leadership (X1) has an influence on Employees’ Performance (Y), with the results of T count (9,525) > T table (2,003), Compensation (X2) has an influence on Employees’ Performance (Y), with the result –T count (-4.108 ) < -Table (-2.003), and Job Placement (X3) have an influence on employees’ performance (Y), with the result of T count (4.745)> T table (2.003). And simultaneously Leadership, Compensation, and Work Placement have an influence on Employees’ Performance at PT. Bakti Nugraha Yuda (Energy) PLTU Baturaja, with the results F count (50,419)> F table (2.77). The coefficient of determination (R Square) is 0.715. This shows that the influence of leadership, compensation and work placement on employees’ performance at PT. Bakti Nugraha Yuda (Energy) PLTU Baturaja, amounting to 71.5% while the remaining 28.5% is influenced by other variables that are not explained in this study.